PERBANDINGAN PRODUK EMAS DIGITAL DAN CICILAN EMAS DI BANK SYARIAH INDONESIA - Daffa Rezaldo, Ahmad; Warsiyah, Warsiyah; Pandahayesti Saputeri, Noorikha; Fakhrurozi, Moh (Jurnal Dinamika Ekonomi Syariah, 2025)
This study aims to compare digital gold products and gold installments offered by Bank Syariah Indonesia, focusing on their advantages, disadvantages, and relevance to customer needs. The scope of the research includes an analysis of the characteristics, transaction mechanisms, and consumer preferences for the two products. The method used is qualitative descriptive with data collection techniques through interviews, observations, and documentation. The results show that digital gold offers transaction flexibility and high liquidity, while gold installments provide physical ownership and protection against price fluctuations. However, digital gold is more susceptible to technological risks, while gold installments require a long-term commitment to payment. The conclusion of this study states that both products have advantages that can be adjusted to the goals and risk profile of each customer, so it is important for Bank Syariah Indonesia to continue to improve services and education related to gold investment.